2004
DOI: 10.1053/j.semtcvs.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Lung preservation

Abstract: Better understanding of the mechanisms of ischemia-reperfusion injury, improvement in the technique of lung preservation, and the recent introduction of a new preservation solution specifically developed for the lungs have helped to reduce the incidence of primary graft dysfunction after lung transplantation. Currently, the limitation in extending the ischemic time is more often related to the increasing use of non-ideal lung donors rather than to poor lung preservation. In this review, we have focused our att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 59 publications
0
9
0
1
Order By: Relevance
“…Similar to other investigations, we have then used a single lung transplantation procedure [ 39 , 40 ]. Lung function early after reperfusion has been carefully monitored, as reperfusion injury is generally considered an outcome measure in lung preservation studies [ 41 ]. For this reason, based on the known effects of perfusion and ventilation on ischemia-reperfusion lung injury [ 42 , 43 ], meticulous attention was given to the reperfusion protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other investigations, we have then used a single lung transplantation procedure [ 39 , 40 ]. Lung function early after reperfusion has been carefully monitored, as reperfusion injury is generally considered an outcome measure in lung preservation studies [ 41 ]. For this reason, based on the known effects of perfusion and ventilation on ischemia-reperfusion lung injury [ 42 , 43 ], meticulous attention was given to the reperfusion protocol.…”
Section: Discussionmentioning
confidence: 99%
“…8,40,41,114,115 Several therapeutic agents have been investigated in an effort to reduce the incidence of PGD, including 5 (1) agents replacing endogenous cytoprotective substances including prostaglandins, nitric oxide (NO), surfactant, endotheliumderived relaxing factor, and adenosine; (2) agents inhibiting proinflammatory mediators including platelet activating factor 1 inhibitor and inhibitors of ROS; and (3) agents inhibiting neutrophil and neutrophil-derived mediators including inhibitors of ROS, cytokines (TNF-α, IL-1β), proteases, lipid mediators, adhesion molecules, and complement cascade. 5,8,114,116 However, there have been only a few randomized trials, usually with limited sample sizes. 5 These small trials have failed to definitively demonstrate efficacy and remain an area of intense study, 98,[117][118][119][120][121][122] even though some studies have shown modest improvements in early clinical outcomes with use of inhaled NO (iNO), 98 surfactant, 122 soluble complement receptor 1 inhibitor, 119 and platelet-activating factor antagonist.…”
Section: Preventive Interventionsmentioning
confidence: 99%
“…The preservation of donor lungs during the cold ischemia phase (CIP) is crucial for prognosis after lung transplantation (LTx). The conventional preservation methods for donor lungs include lung preservation solution and perfusion solution, hypothermic preservation (4–8°C), and lung inflation with oxygen or air ( de Perrot and Keshavjee, 2004 ). However, these methods are not sufficient for lung preservation.…”
Section: Introductionmentioning
confidence: 99%